Measurement of the Structure Constant of Refractivity at Optical Wavelengths Using a Scintillometer - Grabner, Martin; Kvicera, Vaclav (Společnost pro radioelektronické inženýrství, 2012)
The structure constant of the atmospheric refractive index is used for characterizing the turbulence strength and for predicting the scintillation of electromagnetic waves in atmosphere. It is measured continuously in Prague using an optical scintillometer. First monthly and seasonal statistics obtained from the data gathered in the summer 2011 are provided. Lognormal distribution parameters are fitted to the empirical cumulative distribution. The hourly statistics of the structure constant show the typical evolution of turbulence strength during a day.
Keywords: Propagation; turbulence; structure constant of refractivity; scintillation.